1995
DOI: 10.1152/ajplung.1995.269.2.l248
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin attenuates increased endothelial monolayer permeability after RGD peptide, anti-alpha 5 beta 1, or TNF-alpha exposure

Abstract: Endothelial permeability can be altered by tumor necrosis factor-alpha (TNF-alpha), a cytokine released in association with inflammation-induced tissue injury. In the subendothelial matrix, fibronectin (Fn) influences endothelial cell adhesion by the interaction of integrins with RGD and non-RGD attachment sites in Fn. We compared the effect of TNF-alpha, RGD-containing peptides (GRGDSP), or antibody to alpha 5 beta 1-integrins on the protein permeability of bovine lung endothelial monolayers as assessed by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 0 publications
0
55
1
Order By: Relevance
“…Evidence that integrins are involved in maintaining this barrier comes from studies showing that treating endothelial monolayers or isolated coronary venules with RGD peptides (small molecules that disrupt interactions between integrins and the ECM) increase their permeability. [43][44][45] The fact that the increased permeability in these in vitro studies is prevented by the addition of soluble fibronectin or vitronectin suggests that interactions between integrins and the ECM influence vessel permeability. From the data we present here, however, we are able to conclude that ␤3-integrin is not essential for maintaining an intact and functional endothelial barrier.…”
Section: Discussionmentioning
confidence: 96%
“…Evidence that integrins are involved in maintaining this barrier comes from studies showing that treating endothelial monolayers or isolated coronary venules with RGD peptides (small molecules that disrupt interactions between integrins and the ECM) increase their permeability. [43][44][45] The fact that the increased permeability in these in vitro studies is prevented by the addition of soluble fibronectin or vitronectin suggests that interactions between integrins and the ECM influence vessel permeability. From the data we present here, however, we are able to conclude that ␤3-integrin is not essential for maintaining an intact and functional endothelial barrier.…”
Section: Discussionmentioning
confidence: 96%
“…Treatment of EC with anti-α 5 β 1 integrin antibody has been reported to increase endothelial monolayer permeability [39,41]. However, the antibodies used in these studies were either human placenta α 5 β 1 goat antiserum [39], or polyclonal antibody with no indication of an ability to specifically block α 5 β 1 integrin function [41].…”
Section: Discussionmentioning
confidence: 99%
“…However, the antibodies used in these studies were either human placenta α 5 β 1 goat antiserum [39], or polyclonal antibody with no indication of an ability to specifically block α 5 β 1 integrin function [41]. Therefore, it is possible that these antibodies, upon binding, activate α 5 β 1 integrin, or other integrins that may not even be Fg receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Cell integrins are transmembrane proteins on the cell surface that adhere to the proteins of the ECM such as collagen, fibronectin, or vitronectin. These and other adhesive proteins contain short peptide sequences such as RGD, REDV, YIGSR, PHSRN, KNEED, and PRRARV, [37][38][39][40][41][42][43][44][45][46][47][48][49] which are bound by the integrins to promote cell adhesion, spreading, and proliferation. Although significant work has been done to attach proteins and peptides to metal oxide particles 21 and silicon oxide on Si wafers, 26 relatively little research has been reported on attachment of polypeptides to macroscopic metallic surfaces.…”
Section: Introductionmentioning
confidence: 99%